Pemanfaatan Petatas dan Pengembangan Usaha Ternak Kelinci di Desa Beteng Kulon Progo - Hernina Puspitasari, Fransiska; Marcellino Azali, Hansen; Marici Hasyanna Simbolon, Angela; Pamungkas Suryo Guritno, Georgeus; Pangarungan Rita, Rencya; Jonathan, Ari; Angandari Sunanto Putri, Emeritha (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Indonesia is an archipelagic country and has diverse natural resources that can be developed and increase the country’s foreign exchange and economy. This natural potential is often found in rural areas that are still developing. One of the village locations not having received much attention is Desa Beteng, Kabupaten Kulon Progo. Petatas and rabbit livestock are the potential and become a business opportunity for local villagers. The team took the initiative to provide socialization about using petatas as raw material for brownies and developing a rabbit livestock business. These things aim to open the horizons of local villagers as alternative livelihoods to improve their economy. The team identified the potential of the village, studied literature, collected data, and determined solutions. Based on these steps, socialization was carried out and it was found that the majority of villagers were not aware of the potential of the business used as a source of their income. The villagers also seemed enthusiastic and some of them who had started a rabbit livestock business inspired others. Likewise with making brownies from petatas, the villagers are serious and active in participating in this socialization. Monitoring these two things in the future needs to be done.